The physiology of drought stress in grapevine: towards an integrative definition of drought tolerance. (20th May 2020) - Gambetta, Gregory A; Herrera, Jose Carlos; Dayer, Silvina; Feng, Quishuo; Hochberg, Uri; Castellarin, Simone D
Abstract : Review of grapevine drought responses and the search for drought-tolerant varieties that can increase the sustainability of viticulture in the context of climate change. Abstract: Water availability is arguably the most important environmental factor limiting crop growth and productivity. Erratic precipitation patterns and increased temperatures resulting from climate change will likely make drought events more frequent in many regions, increasing the demand on freshwater resources and creating major challenges for agriculture. Addressing these challenges through increased irrigation is not always a sustainable solution so there is a growing need to identify and/or breed drought-tolerant crop varieties in order to maintain sustainability in the context of climate change. Grapevine ( Vitis vinifera ), a major fruit crop of economic importance, has emerged as a model perennial fruit crop for the study of drought tolerance. This review synthesizes the most recent results on grapevine drought responses, the impact of water deficit on fruit yield and composition, and the identification of drought-tolerant varieties. Given the existing gaps in our knowledge of the mechanisms underlying grapevine drought responses, we aim to answer the following question: how can we move towards a more integrative definition of grapevine drought tolerance?